The Evaluation of Implementation of Expansion of Pinang Raya District North Bengkulu Regency - Yuni Indah; Faridah Faridah (Journal of Social Science and Humanities, 2023)
The formation of the Pinang Raya District was outlined in the North Bengkulu Regency Regional Regulation Number 7 of 2015 concerning the Formation of the Pinang Raya District, North Bengkulu Regency. Since 2015 the division process has started and now Pinang Raya has become the definitive district. This research is a policy evaluation research that aims to study how the policy process is implemented. The research method used is explorative qualitative . Data collection method is depth interview. The technique of determining the sample/informant is porposive sampling. Data analysis used the Miles and Huberman method. Based on the results of the study it can be concluded that the mechanism for the division of Pinang Raya District, North Bengkulu Regency has been carried out in accordance with the provisions of the Law of the Republic of Indonesia Number 23 of 2014 concerning Regional Government and Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 19 of 2008 concerning Districts. The mechanism for the expansion of Pinang Raya District, North Bengkulu Regency, began with the aspirations of the Ketahun District community to form a new sub-district in accordance with community needs in development, service and community empowerment. Aspirations that received support from political actors and the District Government were followed by the formation of a sub-district expansion committee and the submission of the proposal for the expansion of the Pinang Raya District to the North Bengkulu Regent through the Ketahun District Head in the form of a proposal. Based on this proposal, the North Bengkulu Regency Government checked the eligibility and after fulfilling the expansion requirements as stipulated in the applicable laws and regulations and set forth in the North Bengkulu Regency Regional Regulation Number 7 of 2015